Students’ Perceptions of Online-Based Guidance and Counseling Services: A Qualitative Phenomenological Study - Rumani, Risza Presty (Journal of Therapia, 2025)
The digital transformation of education has led to the increasing implementation of online-based guidance and counseling services in schools. While these services are often promoted as flexible and accessible solutions, their effectiveness is frequently evaluated through technical or quantitative indicators, providing limited insight into students’ lived experiences. This study aims to explore students’ perceptions of online-based guidance and counseling services, identify relational, technological, and psychosocial factors shaping these perceptions, and analyze their implications for engagement and service continuity. Employing a qualitative interpretative phenomenological design, this study involved in-depth semi-structured interviews with junior and senior high school students who had participated in online counseling services. Data were analyzed using interpretative thematic analysis to capture patterns of meaning derived from students’ experiences. The findings indicate that students’ perceptions of online-based guidance and counseling are shaped by accessibility, flexibility, emotional safety, and the perceived depth of interaction. Counselor–student relational quality, clarity of empathetic communication, technological stability, confidentiality, and psychosocial support emerged as central determinants of positive engagement. Conversely, technological disruptions, privacy concerns, and weak relational dynamics contributed to negative perceptions and reduced participation. This study concludes that the success of online-based guidance and counseling services depends not only on technological infrastructure but also on pedagogical, relational, and psychosocial considerations. Integrating students’ subjective perspectives is essential for developing online counseling practices that are responsive, trustworthy, and sustainable.